2015
DOI: 10.1515/cipms-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

A chemical activity evaluation of two dental calcium silicate-based materials

Abstract: Calcium silicate-based materials are interesting products widely used in dentistry. The study was designed to compare the chemical reaction between analyzed two preparates and dentin during cavity lining. In our work, dentinal discs were prepared from human extracted teeth filled with Biodentine and MTA+. The samples were then analyzed by way of SEM, EDS and Raman spectroscopy. The obtained results revealed differences in elemental composition between both materials. Biodentine showed higher activity in contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“… 24 However, only a few studies have investigated the clinical efficacy of this MTA+. 16 In this study, MTA+ demonstrated a success rate of 86% after 36 months, which was similar to most studies performed with conventional MTA. In addition, all of the calcium silicate derivatives were found to be better than the calcium hydroxide preparations in both clinical and radiographic examinations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“… 24 However, only a few studies have investigated the clinical efficacy of this MTA+. 16 In this study, MTA+ demonstrated a success rate of 86% after 36 months, which was similar to most studies performed with conventional MTA. In addition, all of the calcium silicate derivatives were found to be better than the calcium hydroxide preparations in both clinical and radiographic examinations.…”
Section: Discussionsupporting
confidence: 87%
“… 21 In this manner, bioceramics have been produced, necessitating the revision and/or modification of traditional MTA. 14 , 16 , 22 Nanoparticle insertion to the base of conventional MTA facilitates preparation and increases the sealing process, strength, elasticity and homogeneity of the material. In this study, two novel modified calcium silicate materials as well as calcium hydroxide materials were used as pulp-capping agents and were evaluated in terms of sealing, restoring the vitality of the pulp and inducing the DBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies of other authors have shown similar effects of MTA when used to cover pulp directly [13]. In both groups, total dentin bridge formation was observed and no pulp inflammation was present, suggesting Biodentine as an alternative to MTA [4,5].…”
Section: Age-related Changes In Endodontiumsupporting
confidence: 59%